Poderes instrutórios do juiz: proposta de releitura à luz de aspectos do CPC de 2015 - Pedro Henrique Magalhães Lima (2024)
The Civil Procedure Code of 2015 brought new ideas that modified, to a certain extent, the process model in force in our legal system. The figure of the judge becomes closer to the parties and to the objectives pursued by them, and the process seeks no more to serve the jurisdiction, but turn its attention to the users of the judicial service. Considering this reality, this work seeks to verify whether - with the greatest openness to private autonomy, with the emphasis given to the characteristic in dispute, if could be exercised under one´s discretion or not, whether the principle of cooperation, and the relationship between pretrial measures, estoppel and the rules of distribution of the burden of proof – there are a new limits to the power of evidentiary initiative of judges.